2016
DOI: 10.1139/bcb-2015-0135
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic role of a synthesized calcium phosphate nanocomposite material on hepatocarcinogenesis in rats

Abstract: Nanotechnology research is booming worldwide, and the general belief is that medical and biological applications will form the greatest sector of expansion over the next decade. With this in mind, this study was designed to evaluate the therapeutic effects of a synthesized tricalcium phosphate nanocomposite material (nano-TCP) on hepatocarcinoma in a rat model, as initiated with diethylnitrosamine (DEN) and promoted with phenobarbital (PB). Hepatocarcinoma was induced with intraperitoneal injections of DEN (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…Previous studies have shown that other biochemical proteins, such as MMP-9 and prolactin, are altered during the labor process. Our study found a similar change, but other factors, such as ethnic differences and analysis methods, may account for the difference [2123]. Since this study included a relatively large sample and the findings are consistent with the existing literature, this conclusion could result in a single indicator being used to estimate delivery; however, the sensitivity and specificity of the predictions are unsatisfactory.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown that other biochemical proteins, such as MMP-9 and prolactin, are altered during the labor process. Our study found a similar change, but other factors, such as ethnic differences and analysis methods, may account for the difference [2123]. Since this study included a relatively large sample and the findings are consistent with the existing literature, this conclusion could result in a single indicator being used to estimate delivery; however, the sensitivity and specificity of the predictions are unsatisfactory.…”
Section: Discussionsupporting
confidence: 85%
“…In total, it was found that nano-TCP is a good candidate for curing hepatocarcinoma completely and presenting a new choice for patients to receive healthy, fast, and effective treatment. 37 Another example of a green medical compound is NP formulations with chitosan. Chitosan-graphene oxide (GO) green nanocomposite films were prepared by mixing aqueous chitosan solutions and GO in dilute acetic acid as a solvent.…”
mentioning
confidence: 99%